MR-compatibility of a high-resolution small animal PET insert operating inside a 7 T MRI. (25th October 2016) - Thiessen, J D; Shams, E; Stortz, G; Schellenberg, G; Bishop, D; Khan, M S; Kozlowski, P; Retière, F; Sossi, V; Thompson, C J; Goertzen, A L
Abstract: A full-ring PET insert consisting of 16 PET detector modules was designed and constructed to fit within the 114 mm diameter gradient bore of a Bruker 7 T MRI. The individual detector modules contain two silicon photomultiplier (SiPM) arrays, dual-layer offset LYSO crystal arrays, and high-definition multimedia interface (HDMI) cables for both signal and power transmission. Several different RF shielding configurations were assessed prior to construction of a fully assembled PET insert using a combination of carbon fibre and copper foil for RF shielding. MR-compatibility measurements included field mapping of the static magnetic field ( B 0 ) and the time-varying excitation field ( B 1 ) as well as acquisitions with multiple pulse sequences: spin echo (SE), rapid imaging with refocused echoes (RARE), fast low angle shot (FLASH) gradient echo, and echo planar imaging (EPI). B 0 field maps revealed a small degradation in the mean homogeneity (+0.1 ppm) when the PET insert was installed and operating. No significant change was observed in the B 1 field maps or the image homogeneity of various MR images, with a 9% decrease in the signal-to-noise ratio (SNR) observed only in EPI images acquired with the PET insert installed and operating. PET detector flood histograms, photopeak amplitudes, and energy resolutions were unchanged in individual PET detector modules when acquired during MRI operation. There was a small baseline shift on the PET detector signals due to the switching amplifiers used to power MRI gradient pulses. This baseline shift was observable when measured with an oscilloscope and varied as a function of the gradient duty cycle, but had no noticeable effect on the performance of the PET detector modules. Compact front-end electronics and effective RF shielding led to minimal cross-interference between the PET and MRI systems. Both PET detector and MRI performance was excellent, whether operating as a standalone system or a hybrid PET/MRI.